Pengaruh Bermain Plastisin Terhadap PerkembanganKreativitas Anak Di Tk Negeri Satap Desa Sibargot - Rina Syahfitri; Leli Hasanah Lubis; Ismi Yulizar (Insan Zenius Ilmiah, 2024)
This study aims to determine the effect of the questionand-answer method on the language development of early childhood at RA Al-Wafi Bulungihit Village. This type of research uses quantitative research (Quasi Experiment) with a research sample using population sampling techniques. The RA class serves as the control class where the researcher conducts the learning process using the conventional learning model (lectures, question and answer, discussions) with teachercentered learning activities. The RA Group B class serves as the experimental class taught using the question and answer method. The research instrument used observation sheets and documentation conducted by RA group B children. The data analysis technique used was the paired t-test with a significance level of α=0.05. The results of the hypothesis test for the Post Test data using the question-and-answer method showed that tobserved > t-table (3.378 > 1.895). Thus, Ha is accepted and H0 is rejected. Therefore, there is an influence of the question-andanswer method on the language development of early childhood at RA Al-Wafi Bulungihit Village.